Assessing vitamin D related genetic variants, status, and influence factors in pregnant women in Eastern and Central China. Issue 8 (18th June 2020) - Qiu, Xiaofei; Chen, Xinhao; Zuo, Shangming; Ji, Yuan; Wen, Zheng; Wei, Linna; Wu, Shouxin; Diao, Le; Li, Bo; Zhao, Jiangman; Chen, Tianrui
Abstract: Vitamin D deficiency has recently become a global public health problem. However, it is still unclear if gene polymorphisms in the vitamin D pathway influence vitamin D levels among pregnant women in Eastern and Central China. The objective of this study was to assess factors influencing vitamin D levels in pregnant women. A total of 326 participants in Shandong and Henan provinces in China were enrolled from August 2017 to April 2019. Serum 25(OH)D levels and single nucleotide polymorphisms (SNPs) in the vitamin D pathway were measured using the blood samples collected in the first trimester, second trimester, and third trimester. Data on demographics, lifestyle, and health behavior were collected using a questionnaire. Statistical analyses were performed using the R software. The prevalence of 25(OH)D deficiency was significantly more severe in pregnant women. The average 25(OH)D value of all enrolled pregnant women was 14.57 ± 7.21 ng/ml (deficiency). Only 15 (4.60%) participants had a 25(OH)D concentration ≥30 ng/ml (sufficient). The prevalence of four ranks of vitamin D levels from severe 25(OH)D deficiency to 25(OH)D sufficiency (<10, 10–20, 20–30, and ≥30 ng/ml) was 29.14%, 52.45%, 13.80%, and 4.60%, respectively. Variants of GC (rs1155563) and CYP24A1 (rs6013897) were significantly associated with both 25(OH)D concentrations and vitamin D deficiency among pregnant women, respectively. Our findings suggest that pregnant women in Eastern and Central China are at high risk of vitamin D deficiency. Genetic mutants in the vitamin D pathway (GC and CYP24A1) were significantly associated with 25(OH)D levels in pregnant women in Eastern and Central China. Abstract : Results of this study showed that pregnant women were at high risk of vitamin D deficiency in Eastern and Central China. Serum 25(OH)D level was influenced by BMI, physical activity time, vitamin D intake, and gene polymorphisms in vitamin D pathway (rs1155563 in GC and rs6013897 in CYP24A1) among pregnant women. Vitamin D supplementation could modify this effect of gene polymorphisms.